The Accounting and Legal Issues of Capital Reserve, with Particular Emphasis on Capital Increase by Share Premium - Böcskei, Elvira; Vértesy, László; Bethlendi, András (Public Finance Quarterly, 2020)
The type of capital market transaction in which external investors become the members of an undertaking through capital increase by share premium is frequent in everyday business life. We confirmed the significance of the use of the capital reserve for the purposes of maintaining the solvency of an undertaking by using a descriptive statistical analysis. Based on the interpretation of the legal regulation, and the analysis of the accounting and legal practice we found that the Hungarian accounting and legal regulation on capital reserve in force does not ensure sufficient protection and transparency, which weakens social and business trust in business associations. For this reason we would consider it useful from an accounting perspective if capital reserve, similarly to subscribed capital called but not paid, could be paid subsequently, and if it was shown in a separate line of the balance sheet as long as the payment is not made, and if the supplementary notes also contained an obligation to provide information in that regard. Legal risks can be reduced if the arbitral tribunal’s clause is included in the memorandum of association or syndicate contract in the case of capital increase by share premium. The excessive length of proceedings and capital shortfalls may jeopardise the success of the undertaking as a whole. It would strengthen the operation of the economy and legal certainty if the Court of Registration registered capital increase by share premium only when the capital reserve has already been paid in a verified manner in addition to the subscribed capital.